2023
DOI: 10.1007/s00167-023-07575-w
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell implantation provides short‐term clinical improvement and satisfactory cartilage restoration in patients with knee osteoarthritis but the evidence is limited: a systematic review performed by the early‐osteoarthritis group of ESSKA‐European knee associates section

Hamid Rahmatullah Bin Abd Razak,
Katia Corona,
Trifon Totlis
et al.

Abstract: Purpose Implantation of mesenchymal stem cells (MSCs) is a potential cell-based modality for cartilage repair. Currently, its clinical use largely surrounds focal cartilage defect repair and intra-articular injections in knee osteoarthritis. The MSCs’ implantation efficacy as a treatment option for osteoarthritis remains contentious. This systematic review aims to evaluate studies that focused on MSCs implantation in patients with knee OA to provide a summary of this treatment option outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the clinical trials related to cartilage repair suffer, for instance, from the inclusion of a relatively low number of patients, non-standardized treatments regarding the source of MSCs, their cell isolation methods and cellular dosage [ 30 ]. Still, at least short-term clinical improvements were observed in a recent systematic review of MSC implantation outcomes in patients with knee OA [ 31 ].…”
Section: Cartilage Repair Methodsmentioning
confidence: 99%
“…However, the clinical trials related to cartilage repair suffer, for instance, from the inclusion of a relatively low number of patients, non-standardized treatments regarding the source of MSCs, their cell isolation methods and cellular dosage [ 30 ]. Still, at least short-term clinical improvements were observed in a recent systematic review of MSC implantation outcomes in patients with knee OA [ 31 ].…”
Section: Cartilage Repair Methodsmentioning
confidence: 99%
“…Sialic acids are negatively charged sugars expressed at the terminal positions of N-and O-linked oligosaccharides, which are attached to cell surfaces or secreted glycoproteins. As a result of their non-reducing terminal position, sialic acids are involved in highly specific recognition phenomena [133,134] [ [116][117][118][119][120][121][122] predominantly express α-2-6-specific sialyltransferases and α-2-6-linked sialic acid residues in glycoprotein N-glycans [135]. Interestingly, inflammation stimuli induced a shift from α-2-6-linked towards α-2-3-linked sialic acid, suggesting that α-2-6-linked sialic acid can be used as a biomarker for quality control in amplified human cartilage.…”
Section: Autologous Cartilage/chondrocyte Implantationmentioning
confidence: 99%
“…Furthermore, MSCs are readily available, as they can be isolated from various tissues, including but not limited to bone marrow, adipose tissue, and teeth; they are able to multiply rapidly in vitro , undergoing several to a dozen passages ( Li and Wang, 2022 ). Importantly, clinical trials from different countries have demonstrated the safety of MSCs, as evidenced by the fact that no allergic or severe adverse reactions were observed up to years after years of transplantation ( Arango-Rodríguez et al, 2023 ; Razak et al, 2023 ; Xie et al, 2023 ). Therefore, treatment of MSCs could offer significant potential in treating tissue damage and functional disorders.…”
Section: Introductionmentioning
confidence: 99%